An Optimal Measurement Strategy to Beat the Quantum Uncertainty in Correlated System. Issue 9 (21st July 2020) - Li, Jun‐Li; Qiao, Cong‐Feng
Abstract: Uncertainty principle is an inherent nature of quantum system that undermines the precise measurement of incompatible observables and hence the applications of quantum theory. Entanglement, another unique feature of quantum physics, may help to reduce the quantum uncertainty. In this paper, a practical method is proposed to reduce the one party measurement uncertainty by determining the measurement on the other party of an entangled bipartite system. In light of this method, a family of conditional majorization uncertainty relations in the presence of quantum memory is constructed, which is applicable to arbitrary number of observables. The new family of uncertainty relations implies sophisticated structures of quantum uncertainty and non‐locality, that are usually studied by using scalar measures. Applications to reduce the local uncertainty and to witness quantum non‐locality are also presented. Abstract : An optimal measurement strategy is found that can be used to reduce the local uncertainty, break the quantum uncertainty relation, and distinguish quantum non‐localities. Using the majorization lattice, the optimal measurement strategy is explicitly constructed and the resulting conditional majorization relation in the presence of quantum memory enables to distinguish the quantum steering with infinite‐measurement settings.